Diagnostics and prophylaxis of respiratory tract infections – the latest findings - Brydak, Lidia B. (Przewodnik Lekarza/Guide for GPs, 2007)
According to the WHO, respiratory viruses are the pathogens infecting people most frequently. Some of them are grave health hazards resulting in serious illnesses with complications and death, especially in the case of influenza. As research methods develop, in particular molecular biology, other pathogens of various virulence will be identified. Samples from the upper respiratory tract should be tested multidirectionally for many possible causes. Influenza vaccination is the cheapest and the most effective method of fighting this serious respiratory pathogen. Currently, the only new antiviral drugs for respiratory infections are zanamivir and oseltamivir, recommended for treatment and prophylaxis of influenza A and B.